Water use strategies of Ferula bungeana on mega-dunes in the Badain Jaran Desert - Qin, Jie; Si, Jianhua; Jia, Bing; Zhao, Chunyan; Zhou, Dongmeng; He, Xiaohui; Wang, Chunlin; Zhu, Xinglin (Frontiers in Plant Science, 2022)
Ephemeral plants in desert ecosystems have formed special water use strategies under long-term natural water stress. In order to explore the water use strategies of desert ephemeral plants under natural extreme drought conditions, we investigated the water absorption sources, water potential, hydraulic conductivity and water use efficiency of Ferula bungeana at different heights of the mega-dunes in the Badain Jaran Desert during an extreme drought period. Our results showed that: (1) F. bungeana mainly absorbed most of its water (80.47±4.28%) from 0-60 cm soil layers. With the change of growing season, the source of water absorption changed from 0-30 cm soil layer to 30-60 cm soil layer. (2) The water potential of leaves, stems and roots of F. bungeana exhibited obvious diurnal and monthly variations, which were restricted by water availability and hydraulic conductivity of different parts of the plant; (3) The root hydraulic conductivity of F. bungeana was much greater than the canopy hydraulic conductivity, both of which had significant diurnal and monthly variation; (4) The water use efficiency of F. bungeana under extreme drought conditions was relatively high, and the water use efficiency was higher in the early and late growing seasons. Variations in water availability lead to the regulation of water uptake by F. bungeana and the adjustment of internal water conduction, which changed its water use efficiency. The water use strategies of F. bungeana was mainly related to its growth stage, but has little to do with its distribution positions on mega-dunes. Our findings on water use of ephemeral plants refine the adaptive mechanisms of ephemeral plants in desert habitats and provide a theoretical basis for species selection in the restoration and reconstruction of desert ecosystems.